What Have We Learned from the Enterprise Surveys Regarding Access to Credit by SMEs? - Kuntchev, Veselin; Ramalho, Rita; Rodriguez-Meza, Jorge; Yang, Judy S. (World Bank, Washington, DC, 2014)
Using a unique firm level data set -- the Enterprise Surveys -- this paper develops a new measure of credit-constrained status for firms using hard data instead of perceptions data. The paper classifies firms into four ordinal categories: Not Credit Constrained, Maybe Credit Constrained, Partially Credit Constrained, and Fully Credit Constrained to understand the characteristics of the firms that fall into each group. Comparable data from the Enterprise Surveys for 116 countries are used to look at the relationship between firm size and credit-constrained status. First, the analysis finds that small and medium enterprises are more likely to be credit constrained (either partially or fully) than large firms. Furthermore, small and medium enterprises finance their working capital and investments mainly through trade credit and informal sources of finance. These two results hold to a large extent in all the regions of the developing world. Second, although size is a significant predictor of the probability of being credit constrained, firm age is not. Third, high-performing firms, as measured by labor productivity, are less likely to be credit constrained. This result applies to all firms but is not as strong for small firms as it is for large and medium firms. Finally, in countries with high private credit-to-gross domestic product ratios, firms are less likely to be credit constrained. Given the importance of access to credit for firm growth and efficiency, this paper confirms that throughout the developing world access to credit is inversely related to firm size but positively related to productivity and financial deepening in the country.